Penerapan model pembelajaran CTL untuk meningkatkan pemahaman konsep IPA materi gaya - Siti Choerun Nisa; Sylvia Sylvia Rabbani; Linda Hania Fasha (COLLASE (Creative of Learning Students Elementary Education), 2026)
The main problem in the research is the low understanding of science concepts in style material among fourth-grade students. This research aims to analyze the results of increasing the ability to understand science concepts in style material by applying the Contextual Teaching And Learning (CTL) learning model to students, and the obstacles in implementing the CTL learning model. The research method uses quantitative methods that focus on student learning outcomes. The research object used 35 students with data obtained from pretest and posttest tests. Based on the results of the research that has been carried out, it can be concluded that the results obtained from the quantitative data are an increase in students' ability to understand the science concept of style material as seen from the pretest and posttest with the normality test, homogeneous test and paired sample t-test which obtained a significant value that there is an increase in the ability to understand science concepts in style material by applying the Contextual Teaching And Learning (CTL) learning model. The results obtained from responses to the obstacles experienced by teachers and students are that teachers are constrained in conditioning the class, presenting concrete media as a whole, and allocating learning time. Meanwhile, students' obstacles lie in external factors, namely their friends and the allocation of learning time.